2005
DOI: 10.1111/j.1460-9568.2004.03829.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase (MMP)‐12 expression has a negative impact on sensorimotor function following intracerebral haemorrhage in mice

Abstract: We investigated the role of matrix metalloproteinases (MMPs) in a mouse model of intracerebral haemorrhage (ICH). Transcripts encoding nine of the 23 known mammalian MMPs were measured. MMP-12 levels were the most elevated. To evaluate the role of MMP-12 in ICH, haemorrhages were induced in wild-type (WT) and MMP-12 null mice. The results show that MMP-12 null mice exhibited significant functional recovery of forelimb reaching and reduced dependence on the ipsilateral forelimb compared to WT mice. There was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 44 publications
3
69
0
Order By: Relevance
“…26,27 As in the present study, the cylinder test of forelimb function shows a very modest cylinder effect in cICH in rats 28 or a short-term effect in cICH in mice. 29 Some of the effects of bICH and cICH in the mouse are distinct to that seen in the rat. Behavioral deficits persist for a greater period in rat cICH 26,30 than in the mouse.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 As in the present study, the cylinder test of forelimb function shows a very modest cylinder effect in cICH in rats 28 or a short-term effect in cICH in mice. 29 Some of the effects of bICH and cICH in the mouse are distinct to that seen in the rat. Behavioral deficits persist for a greater period in rat cICH 26,30 than in the mouse.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in EAE, transcripts encoding 11 of 20 MMPs were significantly elevated in the spinal cord at peak disease compared with controls. 42 Multiple MMPs are also increased in the early periods after spinal cord trauma, 43,44 intracerebral hemorrhage [45][46][47] and ischemic strokes. 48,49 As the CNS encounters most MMPs only in low amounts in the normal situation, the concurrent and significant increase of multiple MMPs with the potential for widespread proteolysis must have undue consequences.…”
Section: When the Good Guys Go Badmentioning
confidence: 99%
“…Our previous report 45 revealed that the levels of all MMP members analyzed did not differ between naïve wild-type or MMP-12 Ϫ/Ϫ mice, or when these mice were subjected to an intracerebral hemorrhage insult. We determined if this was also the case in EAE-afflicted mice.…”
Section: Altered Processing Of Opn In Mmp-12 ϫ/ϫ Micementioning
confidence: 99%
“…In previous work, we found that the levels of all MMP members analyzed did not differ between naïve wild-type or MMP-12 Ϫ/Ϫ mice. 45 EAE was induced in female wild-type, OPN Ϫ/Ϫ , MMP-12 Ϫ/Ϫ , or OPN/MMP-12 Ϫ/Ϫ mice on C57BL/6 background, aged 8 to 9 weeks, by subcutaneously injecting 100 g myelin oligodendrocyte glycoprotein (MOG) in Complete Freund's Adjuvant (Difco Laboratories, Detroit, MI). Intraperitoneal pertussis toxin (0.4 g/200 l; List Biological Labs, Hornby, ON) was administered on days 0 and 2.…”
Section: Disease Induction and Eae Analysismentioning
confidence: 99%